p53 overrides METTL5 loss–induced tumor suppression via mitochondrial respiration - Guozhi Li; Qiujie Li; Jun Zhang; Yifei Huang; Wenjun Tao; Yali Cheng; Jiaju Sun; Jingying Yuan; Rui Zhang; Xiao-Min Liu; Jun Zhou (Proceedings of the National Academy of Sciences, 2026)
The tumor suppressor p53 is pivotal in repressing tumorigenesis under physiological conditions. Paradoxically, we find that wild-type (WT) p53 plays an oncogenic role in relieving METTL5 depletion–caused cancer regression by sustaining mitochondrial respiration. The methyltransferase METTL5 is upregulated in non–small cell lung cancer (NSCLC) and associated with advanced tumor grade and poor prognosis. Depletion of METTL5 impairs NSCLC cell proliferation and migration in vitro and in vivo, with p53-null cells displaying enhanced sensitivity. While METTL5 -depletion inhibits cytoplasmic translation in both p53-WT and p53-null cells, only cells lacking p53 exhibit severe tumor regression due to defective mitochondrial protein synthesis and consequent respiratory dysfunction. Mechanistically, p53 binds 5’UTR of TOMM40 , the crucial gatekeeper of mitochondrial protein import, to enforce its exclusion from translation. METTL5 loss promotes p53 nuclear retention via inhibiting MDM2-mediated p53 ubiquitination, alleviating its translational suppression of TOMM40 , and supporting oxidative phosphorylation. Remarkably, the combination targeting of p53 and METTL5 synergistically attenuates the proliferation and migration in p53-WT cancer cells. Our study elucidates the essential role of p53 in supporting tumor viability upon METTL5 deficiency by maintaining mitochondrial respiration. Meanwhile, it provides a molecular foundation for developing therapeutic strategies regarding cancers with WT p53.